Single step electrosynthesis of NiMnGa alloys. (20th June 2016) - Özkale, Berna; Mushtaq, Fajer; Fornell, Jordina; Chatzipirpiridis, George; Martin, Lukas H.J.; Sort, Jordi; Müller, Carlos M.; Pellicer, Eva; Nelson, Bradley J.; Pané, Salvador
Abstract: An electrochemical synthesis route for NiMnGa alloys is presented. Thin films of NiMnGa were fabricated by single step electrodeposition from aqueous electrolytes using direct current over a range of current densities. By electrolyte tuning, homogeneous films with high Ga and Mn content could be achieved at current densities as high as −400 mA cm −2 . Detailed compositional analysis of the alloys showed that growth was homogeneous and oxygen content was minimized. Films plated at very low current densities were found to be nanocrystalline/amorphous. In order to obtain fully crystalline samples, thermal annealing was carried out. Mechanical characterization was assessed by nanoindentation, and the effect of Ga content on mechanical properties was investigated.